PEMBERDAYAAN KELOMPOK TANI ASUNG KAMULYAN MELALUI INOVASI TEKNOLOGI MESIN PEMANEN PADI - Hidayat, Khoirul; Firmansyah, R. Arief; Yaskun, Mohammad (Jurnal Likhitaprajna, 2025)
Asung Kamulyan Farmer Group is one of the farmer groups in Sidomulyo Village, Mantup District, Lamongan Regency. Rice harvesting in Sidomulyo Village is done traditionally using a sickle and then threshed using a threshing machine to separate the rice grains from the rice stalks which produces waste called straw. Problems in the production aspect, partners experience difficulties during harvesting activities because the number of available harvesters decreases. The method used is the action research method, namely taking action based on the results of observations and discussions with partners. The results of this activity, from the production aspect, there is an ergonomic rice harvesting machine used by the community which can increase harvesting productivity from 2 m²/minute to 10 m²/minute or an increase of 5 times. In addition, there is an SOP for operation, maintenance, and resolution of other obstacles (troubleshot) as material that can be used to ensure that the use of the technology provided continues to provide benefits. In addition, partners can arrange the rental schedule for ergonomic harvesting machines and their financial management, so that farmer groups have other sources of income from renting and maintaining harvesting machines